A vision-based vehicle follower Navigation using fuzzy logic Controller/ Nurul Izzati Mohd Saleh - Awam, Pusat Pengajian Kejuruteraan (2017)
This research presents the vision-based approach to ground vehicle follower navigation. The system utilize fuzzy logic controller to navigate itself. There are two components of the prototype which is the vision system component and the actuating component. The vision system component is controlled by a microprocessor, Raspberry Pi. The actuating component is controlled by the microcontroller, Arduino Mega. The vision system component utilizes Camshift tracking and the illumination inconsistency is corrected using histogram equalization. The consequent parameters obtained from the pilot test is used to design the appropriate fuzzy membership functions and rules. The are two type of rules tested. The first one which is method A utilized 15 rules of fuzzy logics whereas the second method which is method B introduced three additional hedges rules to the existing 15 rules. The results show that both methods produce desirable results as the prototype is able to navigate itself to follow the lead vehicle with Method B produces the best results.